Application of hybrid membrane system to treat simulated batik wastewater / Hamidreza Rashidi - Rashidi, Hamidreza (2015)
Rapid growth of the population and domestic industrialization activities have resulted in wastewater production; one of the significant harmful impacts towards the environment. Textile industries have been recognized to be among the largest water consumers amid the industries, as well as hazardous wastewater generators. Furthermore, as a result of regional cultural preferences, popular particular textile industries like batik, in South East Asian regions especially in Malaysia, discharge untreated wastewaters, which contain mainly wax, resin, dyes and fixing agents (sodium silicates) directly to the environment. Accordingly, this study has been conducted to investigate the application of hybrid membrane filtration to treat batik wastewaters. This study consists of the combination of two main treatments namely; the baffle separation tank pre-treatment followed by ultra and nano filtration membranes. The former was applied to remove all undesired physical contaminants from batik wastewaters before the main conventional treatment technique – the hybrid membrane treatment – for removing chemical and physical contaminants from different simulated batik wastewaters. Single and multi-premixed textile fibre reactive dyes namely Remazol turquoise blue 15, Remazol red 194, Remazol yellow 14, Reactive orange 16 and Reactive black 5 with invariant value concentration (16 mg/L), constant value of paraffin wax and resin (7.7 g/L) and sodium silicate (1 g/L) were used. The performance of the hybrid system was evaluated based on wax and heavy metal removal efficiency (%) and rejection of dyes and sodium silicate using COD, pH and conductivity as the indicator parameters. Membrane flux and fouling behaviour in both ultra and nano filtration were investigated. The membrane surface was observed using FESEM technique. Moreover, HPLC tests were used to help verify the achieved results from other analytical methods. The results showed that wax removal efficiency achieved in all the samples from pre-treatment and UF stages was more than 99%. Complete dye rejection in all dye solution samples was achieved. The sodium silicate rejection rate in both single and mixture dye samples were in the range of 45% - 60%. Concentration of heavy metals and COD values in the permeates declined significantly (reached almost total rejection) as compared to the feed solution. The comparison of pH and conductivity values between the feed and permeate samples after each treatment cycle represented distinct decline changes, which were in agreement with the other achieved results (range between 7.2 and 7.7; and < 90.3 S/cm respectively). The achieved results concluded that the presented hybrid membrane treatment technique leads to a higher efficiency rate while remarkably reducing the operational processing time. Ultimately, these outcomes promote a sustainable approach towards the implementation of batik wastewater treatment using the proposed baffle tank system and membrane filtration.